PENA EMAS: A MODEL OF COMMUNITY EMPOWERMENT AND INDEPENDENT PARTICIPATION IN HANDLING STUNTING - Dwipayanti, Puteri Indah; Virgia, Vera; Sari, Kurnia Indriyanti Purnama; Chasanah, Nur; Wardani, Riska Aprilia (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Various national efforts and programs have been launched to overcome the problem of stunting. However, the incidence of stunting still cannot be resolved optimally. One real effort to overcome the problem of stunting is to empower the community itself. In implementing this community empowerment activity, the PRA (Participatory Rural Appraisal) method is used because this method emphasizes the full involvement of partner communities in the program to be carried out. The three program priorities that will be implemented are providing additional food (PMT) to stunted toddlers and toddlers as well as pregnant women with chronic energy deficiency (KEK), increasing knowledge of partner communities through information communication and education (KIE) activities for target groups, and economic empowerment. family. The aim of implementing this activity is to provide assistance and trigger partner communities in overcoming the stunting problem that occurs. A total of 16 people attended the Ecoprint Workshop, and 15 people attended catfish cultivation training. The output targets targeted in implementing this activity include reducing the number of toddlers and toddlers with stunting, increasing hemoglobin levels and upper arm circumference in pregnant women who experience chronic energy deficiency, publishing articles in national journals, and documenting the implementation of community empowerment activities with stunting problems.